Analysis Of Risk Factors For Covid - 19 Patients Using Mechanical Ventilation At Abdul Moeloek Lampung Hospital Year 2021 - Nanang Dismiantoni; Samino; Fitri Eka Sari; Torry Duet Irianto; Nurhalina Sari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Considering that the number of confirmed cases of COVID-19 continues to increase, the Ministry of Health has issued Circular Letter Number HK 02.01/Menkes/ concerning Increasing the Capacity for Treatment of COVID-19 Patients in Hospitals Providing COVID-19 Services Issued 11/2021. This is especially true for patients on ventilators or in isolation rooms. This study aims to analyze the risk factors for COVID-19 patients who use ventilators at Abdul Moerok Hospital, Lampung in 2021. This research is a quantitative study using a cross-sectional design. The research was conducted at Abdul Moerok Regional Hospital from September 2022 to January 2023. The study population included 2,152 COVID-19 patients who were treated in hospital rooms and hospital wards. The sample was 337 people. Medical records are used as research instruments. Data were analyzed using univariate, bivariate and multivariate analysis. Respondents within 8 days after birth were 249 people (73.9%), 207 people (61.4%) had no complications, 250 people (74.2%) had oxygen saturation >90%, and 128 people were using a ventilator. people (38.0%). Relationship between age (p 0.001), gender (p 0.011), duration of Covid-19 disease (p 0.031), Covid-19 patients (p 0.001), and oxygen saturation (p 0.001), use of ventilators in Covid-19 patients. Oxygen saturation is the variable that has the greatest influence on the incidence of mechanical ventilation in Covid-19 patients, with a p-value of 0.001 and an OR of 68.285. It is hoped that the public will increase their knowledge so that they can avoid risk factors that can reduce oxygen saturation and maintain lung function